2018
DOI: 10.1158/0008-5472.can-18-0330
|View full text |Cite
|
Sign up to set email alerts
|

CDK1 Interacts with Sox2 and Promotes Tumor Initiation in Human Melanoma

Abstract: Cancers are comprised of heterogeneous subpopulations with various tumor-initiating capacities, yet key stem cell genes associated with enhanced tumor initiating capacities and their regulatory mechanisms remain elusive. Here we analyzed patient-derived xenografts from melanoma, colon, and pancreatic cancer tissues and identified enrichment of tumor-initiating cells in MHC class I-hi cells, where CDK1, a master regulator of the cell cycle, was upregulated. Overexpression of CDK1, but not its kinase-dead varian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 54 publications
(66 reference statements)
2
75
0
1
Order By: Relevance
“…For instance, SOX2 has been shown to contribute to melanoma metastasis 35 and to be highly expressed in melanomas compared to nevi 36 . In addition, SOX2 regulates survival, self-renewal, and tumorigenicity of human melanoma-initiating cells 11 , 37 and participates in dormancy regulation of melanoma tumor-repopulating cells 38 . SOX2 has been recently related to the acquisition of an aggressive oxidative tumor phenotype endowed with enhanced drug resistance and metastatic ability 39 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SOX2 has been shown to contribute to melanoma metastasis 35 and to be highly expressed in melanomas compared to nevi 36 . In addition, SOX2 regulates survival, self-renewal, and tumorigenicity of human melanoma-initiating cells 11 , 37 and participates in dormancy regulation of melanoma tumor-repopulating cells 38 . SOX2 has been recently related to the acquisition of an aggressive oxidative tumor phenotype endowed with enhanced drug resistance and metastatic ability 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly as previously shown [73], vemurafenib resistance was developed independently from SOX2 expression in drug-naïve cells, however, while in the study of Cesarini et al, SOX2 was strongly upregulated only in one out of three vemurafenib-resistant cell lines, in our study SOX2 upregulation was observed in all six PLXR cell lines. As several reports suggest genetic context-dependent role of SOX2 in melanoma [73][74][75][76][77], regulation of SOX2 expression and the role of this transcription factor in resistant melanoma cells remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…MCM was obtained from supernatants of human metastatic melanoma cells, 1205Lu (obtained from Rockland Immunochemicals, Inc, Limerick, PA), after 24 hours of cultivation in Opti‐MEM I Reduced Serum Media (Life Technologies, Grand Island, NY), and centrifuged at 210 g for 5 minutes . 1205Lu cells were routinely checked for mycoplasma by PCR as previously described, and authenticated using short tandem repeat (STR) analysis by Barbara Davis Center Bioresource Core. To treat PBMCs with MCM or IL‐1β, cells were cultured for 24 hours with complete media containing 10% MCM, 50% MCM, or 10 ng/mL IL‐1β (Life Technologies, Thermo Fisher).…”
Section: Methodsmentioning
confidence: 99%